Legal Protection of Labor in Employment for Termination of Employment Due to the Acquisition of the Company - I Putu Rasmadi Arsha Putra; I Ketut Tjukup; Dewa Gede Pradya Yustiawan (Susbtantive Justice International Journal of Law, 2020)
The emergence of competition makes companies do various things to maintain their existence and the stability of companies in the world of economy. One of the ways the company survives in the agreement is to make an acquisition. In addition to generating profits for the company that acquires the acquiring company, acquiring can also balance employment including termination of employment that is detrimental to workers. The subject matter of this research is protection for workers carried out with the approval and how to solve the problems requested by companies that carry out procurement actions. This research is normative legal research, which is assisted by field research with interview techniques. The agreement used was approval on the invitation (statute approach), conceptual agreement (conceptual approach) and case approach (case approach). Data is collected by literature study, by reading references that are used such as invitation rules, books, journals, which are related to the debate raised, then analyzed by description analysis techniques. Regarding the results obtained in Indonesia's positive law legal protection for workers resulting from acquisitions by companies still relies on the Labor Act, there is no sense of justice for workers when there are terminations due to the acquisition. Termination of employment is resolved by legal action in the form of non-litigation and legal litigation under the Settlement of Industrial Relations Disputes Act. This research is important because the labor law is far from the concept of the Pancasila legal rule in which the Pancasila legal rules always uphold public welfare and social justice in the protection of workers, workers in Indonesia are still underestimated and do not have enough space to protect.